2011
DOI: 10.1063/1.3604519
|View full text |Cite
|
Sign up to set email alerts
|

Isochoric thermal conductivity of solid n-alkanes: Hexane C6H14

Abstract: The isochoric thermal conductivity of solid n-hexane C 6 H 14 has been investigated on three samples of different density in the temperature interval from 100 K to the onset of melting. In all the cases the isochoric thermal conductivity varied following a dependence which is weaker than Λ ∝ 1/Т. The results obtained are compared with the thermal conductivities of other representatives of n-alkanes. The contributions of low-frequency phonons and "diffuse modes" to the thermal conductivity are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…Thermal conductivity experimental data are scarce in the literature, even for the solid and liquid phases of n -alkanes. Most works address n -alkanes with carbon numbers <20. The works of Vélez and co-workers , present data of n -alkanes thermal conductivities, in the liquid and solid phases, in good agreement with results from other studies. ,, These works suggested that n -alkanes have their thermal conductivity enhanced by a factor of 2–3 when passing from the liquid to the solid phase.…”
Section: Introductionsupporting
confidence: 57%
“…Thermal conductivity experimental data are scarce in the literature, even for the solid and liquid phases of n -alkanes. Most works address n -alkanes with carbon numbers <20. The works of Vélez and co-workers , present data of n -alkanes thermal conductivities, in the liquid and solid phases, in good agreement with results from other studies. ,, These works suggested that n -alkanes have their thermal conductivity enhanced by a factor of 2–3 when passing from the liquid to the solid phase.…”
Section: Introductionsupporting
confidence: 57%
“…The associated references are as follows. nCB ( 31 ); VO 2 ( 26 ); K, Zn, Cd, and Hg ( 32 ); c-Se ( 33 ); Ni-Mn-In alloy ( 13 ); C 6 H 14 ( 34 ); Sn, In, and LiNO 3 ( 15 ); C/C 16 H 34 composite ( 17 ); Ge 2 Sb 2 Te 5 ( 27 ); azobenzene polymers ( 14 ). ( D ) Multiple on/off thermal cycles of nanofiber #2 around the phase transition temperature of 440 K.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal conductivity of Cu wire is affected by magnetic field, with experiment at 4.2 K recording thermal conductivity decrease and in proportionality under such fields (and Pure/Compound (H 2 O [35], c-Se [36], C 6 H 14 [37,38], NaF [39]) Passive Low Dimensionality…”
Section: Thermal Conductivity Switches (Tcs)mentioning
confidence: 99%